THE APPLICATION OF GENETIC ALGORITHM IN DEBRIS FLOWS PREDICTION - Chang T.-C.; Chien Y.-H. (My University, 2007)
Debris flows caused serious loss of human lives and damages to properties in Taiwan for the past decades. A number of methods for prediction of debris flows have been studied including numerical method, statistic method, experiment method and neural network method in recent years. This study proposed a genetic algorithm (GA) model for occurrence prediction of debris flows. A total of 154 potential cases of debris flows collected in eastern Taiwan were fed into the GA for training and testing. The average ratio of successful prediction reaching 90.4% demonstrates that the presented GA model can provide a stable and reliable result for prediction of debris flows in the hazard mitigation and guarding system. © 2007 Springer-Verlag.
Keywords: DEBRIS FLOWS; GENETIC ALGORITHM; PREDICTION